On Knowledge (ALPHA. Journal of Arts, Literature and Philosophy, 2002)
On the basis of competing scientific theories, both of a natural and of a social order, this article examines discussions relating to the theory of knowledge that have come from those sciences and whose common objective is the creation of a theoretical platform that would make it possible to go beyond the traditional conception of knowledge as the representation of a reality that is independent of knowledge itself, traditionally known as realism. To this end, a conception of radical constructivism and an existential perspective are confronted in order to evaluate their merits, the radicality of their criticism and the distance of both points of view from modern idealism, the dangers of which need to be avoided.